The spotted flounder, Azygopus flemingi Nielsen 1961 (Pisces: Pleuronectiformes: Rhombosoleidae), from deep waters off New Zealand: a second valid species of Azygopus Norman 1926, with notes on distribution, size, maturity, and ecology - Munroe, Thomas A. (Zootaxa, 2012)
Since its description, Azyygopus Norman, 1926 was considered by subsequent authors to be a monotypic genus in the Or-der Pleuronectiformes comprised only of A. pinnifasciatus Norman, 1926, known from deep waters (90–900 m, usually200–600 m) off the southern and southeastern coasts of Australia. In 1961, a subspecies, A. pinnifasciatus flemingi Niels-en, was described based on three specimens collected at 610 m in the Tasman Sea off the South Island, New Zealand. Fromits description to contemporary literature evaluating its status, recognition of A. p. flemingi as a distinct taxon has beenrejected by all but two studies reporting on Azygopus from New Zealand waters. Until the late 20th century, specimens ofAzygopus had been rarely collected off New Zealand and little was known about these fishes. Over the past 25 years, col-lecting by scientific expeditions and expanding deep-sea fisheries have captured over 195 specimens of Azygopus from avariety of deep-sea locations around New Zealand. Recently-captured specimens of Azygopus collected around New Zea-land and deposited in fish collections have been identified as either A. pinnifasciatus Norman or A. flemingi Nielsen, sug-gesting the possibility that two species of Azygopus occur in New Zealand waters. This study examined the holotype, aparatype, and 25 non-type specimens of A. pinnifasciatus collected off Australia, and the most comprehensive series ofspecimens of Azygopus collected from New Zealand waters. These specimens included the holotype and two paratypes ofA. p. flemingi and 191 other specimens collected from throughout the entire depth range (153–942 m) and representingwide coverage of geographic areas around New Zealand where Azygopus have been collected. Comparisons of these spec-imens indicate that a second species, A. flemingi Nielsen, should be recognized in the genus Azygopus, and that this speciesis the only member of this genus occurring in New Zealand waters. Azygopus flemingi is readily distinguished from A.pinnifasciatus by conspicuous differences in ocularand blind-side color patterns, in numbers of ocular-side pelvic-finrays, total vertebrae, lateral-line scales, and gillrakers on the first gill arch, morphology of blind-side scales and squama-tion patterns, length of blind-side pectoral fins, presence/absence of scales between upper jaw and ventral margin of lowereye, and pigment patterns on dorsal and anal fins of adults. Adult A. flemingi and A. pinnifasciatus are sexually dimorphic in several features. Data on maximum size and size at maturity, and depth of occurrence are summarized for A. flemingi.